2018
DOI: 10.21037/jovs.2017.12.16
|View full text |Cite
|
Sign up to set email alerts
|

Uniportal video-assisted thoracic lung segmentectomy with near infrared/indocyanine green intersegmental plane identification

Abstract: In the era of lung cancer screening and early detection of lung lesions, pulmonary segmentectomy has gained wide acceptance between thoracic community reducing the need of lobectomy for diagnostic purpose and treatment in case of centrally located benign, multiple or undetermined lesions. In rigorously selected patients with stage I non-small cell lung cancer (NSCLC), segmentectomies seem to offer similar survival outcomes rather than lobectomies, but associated with a better conservation of lung function. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Preoperative CT-based planning offers similar operative time, mortality, morbidity, and complication rates with the advantage of identifying difficult surgical cases early [55]. Other studies have demonstrated intraoperative identification of intersegmental planes after segmental artery ligation and distal injection of ICG or indigo carmine dyes [5963]. This approach allows identification of resection planes by naked eye or with NIR fluorescence, potentially enabling safer and effective resection.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative CT-based planning offers similar operative time, mortality, morbidity, and complication rates with the advantage of identifying difficult surgical cases early [55]. Other studies have demonstrated intraoperative identification of intersegmental planes after segmental artery ligation and distal injection of ICG or indigo carmine dyes [5963]. This approach allows identification of resection planes by naked eye or with NIR fluorescence, potentially enabling safer and effective resection.…”
Section: Discussionmentioning
confidence: 99%
“…According to toxicity studies, a 5.0 mg/kg ICG intravenous injection is safe and tolerable. 17 In order to reduce the dose of ICG and improve the safety, we used 0.5 mg/ kg ICG injection and the blue intensity was clear. Maximum blue intensity is gained in about 1 minute, then lasts for 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidences showed that VATS-based segmentectomy has rendered better postoperative pulmonary function and faster postoperative recovery than VATS-based lobectomy. 17 The difficulty of segmentectomy lies in the confirmation of the intersegmental plane. 11 It is important to perform adequate preoperative evaluation such as using 3-dimensional reconstruction of CT images in order to identify the dominant artery and bronchi to the target segment in preoperative planning.…”
Section: Discussionmentioning
confidence: 99%
“…10 This technology has been applied to the demarcation of intersegmental planes for pulmonary segmentectomy and has been reported to be safe and feasible, attracting increasing attention from a multitude of thoracic surgeons. 5,6,[11][12][13][14][15][16][17][18][19] This is a prospective phase I/II clinical study conducted to evaluate NIR image-guided pulmonary segmentectomy after endobronchial ICG injection according to the predetermined assessment items described in Figure 2. NIR fluorescence-guided pulmonary segmentectomy was initially accompanied by the intravenous injection of ICG and NIR thoracoscopy in Japan.…”
Section: Commentmentioning
confidence: 99%